Macroeconomic burden of firearm-related fatality across OECD countries: an estimate of annual and cumulative gross domestic product losses, 2018-30 - Alexander W Peters, MD; Rachel R Yorlets, MPH; Mark G Shrime, MPH; Blake C Alkire (Elsevier, 2019)
Background: In 2015, firearm-related unintentional injuries, physical violence, and self-harm caused over 36 000 deaths and 100 000 injuries in the USA, and over 250 000 deaths worldwide. Of these deaths, more than 64 000 were in OECD countries. Nevertheless, firearm injury risk reduction remains socially and politically controversial. Although the costs of treating firearm injuries has been estimated, little is known about the macroeconomic impact of firearm deaths. Here, we aim to estimate the future macroeconomic burden of deaths in OECD countries. Methods: Using value-of-lost-output methodology, which estimates the macroeconomic burden of deaths in terms of lost economic productivity, we estimated the annual and cumulative gross domestic product (GDP) lost due to firearm-related fatalities from 2018 to 2030 in all 36 OECD countries. We used mortality data from the 2016 Global Burden of Disease study to project mortality rates from 2018 to 2030. We then applied these projections to an adapted version of the WHO EPIC (Projecting the Economic Cost of Ill-health) model to project GDP losses attributable to firearm-related deaths. Findings: Across OECD countries, we estimated macroeconomic losses from firearm mortality at US$272·1 billion in lost economic output between 2018 and 2030 ($124·9 billion from physical violence, $135·7 billion from self-harm, and $11·4 billion from unintentional injury), with $8·0 billion in annual losses in 2018 growing to an estimated loss of $35·9 billion in 2030. This amount represents 0·051% of total estimated 2030 GDP, or $1 lost for every $1944 of potential economic output. The USA is estimated to lose more than other OECD nations, with annual GDP losses of $24·5 billion in 2030, representing 0·10% of US GDP in 2030, and $180·6 billion cumulative losses from 2018 to 2030. Mexico's estimated loss in 2030 is $6·3 billion, which represents 0·20% of Mexican GDP in 2030, and $50·3 billion cumulatively from 2018 to 2030. No other OECD country had estimated cumulative losses greater than $10·6 billion in the study period, nor greater than 0·04% of GDP in 2030. Considered as a proportion of 2030 GDP, the USA's projected losses were 93·0% higher and Mexico's losses were 290·6% higher than the mean proportional losses across all OECD countries in 2030. Interpretation: Firearm-related deaths are expected to cause disproportionately high macroeconomic losses in the USA and Mexico from 2018 to 2030 compared with other OECD countries. These losses represent an important proportion of GDP, and should be considered in broader social, economic, and health policy decisions about firearm regulation. Future studies might consider cost-benefit analyses that weigh the costs of risk reduction interventions against the potential economic savings of reducing firearm mortality. Funding: None.